TEACHER COMPETENCE IN THE DIGITAL ERA A PHENOMENOLOGICAL STUDY - Rustandi, Jajang; Ansori, Muhammad Rizal; Fahlepi, Reza; Iriansyah, Iriansyah; Marliat, Marliat (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to understand teachers' experiences in developing their digital competence in the era of educational digitalization through a phenomenological approach. The research focuses on the factors influencing teachers' digital competence, the challenges they face, and the role of institutional support such as schools, education policies, and professional training. The research method used is qualitative with a phenomenological approach, where data is collected through in-depth interviews with participating teachers and field observations. The data is then analyzed using thematic analysis techniques to identify key themes that emerge from the teachers' subjective experiences. The findings show that teachers' digital competence is influenced by access to technological infrastructure, prior experience with technology, and institutional support. Teachers in urban areas are generally better prepared to face digitalization compared to teachers in remote areas, who experience limitations in technological access. Additionally, relevant professional training and supportive education policies play a crucial role in enhancing teachers' digital competence. However, challenges such as psychological pressure and ethical dilemmas in maintaining social interaction with students also emerge as barriers in this adaptation process. In conclusion, holistic support, both technical and emotional, is essential to help teachers effectively develop their digital competence.